Spiritual Transformation in the Digital Era: A Study of Sufism Dimensions in Angelina Sondakh’s Social Media Content - Tahir, Gustia (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
This study explores the dimensions of Sufism as presented in the social media narratives of Angelina Sondakh, an Indonesian public figure who experienced significant personal transformation. After facing legal challenges and imprisonment, Angelina’s journey towards spiritual introspection and her embrace of Sufi practices became a prominent aspect of her social media presence. Using platforms like Instagram and YouTube, she shares her experiences with Sufism, focusing on themes of inner purification (tazkiyah al-nafs), submission to divine will (tawakal), and mindfulness (muraqabah). This research investigates how these spiritual practices are articulated in the digital space and how they resonate with her followers. Through qualitative analysis of her social media content, the study examines the ways in which Sufism is communicated, the authenticity of her spiritual transformation, and the responses from her audience. The findings suggest that social media can serve as an effective platform for conveying spiritual values, while also presenting challenges related to maintaining authenticity in the public eye. Additionally, this study highlights the potential for Sufism to remain relevant and accessible in the digital age, offering insights into the intersection of spirituality and modern technology. This research contributes to the growing field of digital spirituality and provides a case study on how public figures use social media to engage in personal transformation and promote spiritual teachings.